Low intensity pulsed ultrasound for fractures of the tibial shaft - Griffin, X (BMJ Publishing Group, 2016)
The key characteristic of a clinical researcher is probably the determination to deliver high quality studies despite all the inevitable bumps along the road. As well as the difficulties around funding and maintaining large collaborations that can deliver high impact multicentre studies, there are also more worrying challenges that threaten the robustness of the science. Some are widely recognised, such as publication bias, others are less overt; the reluctance of sponsors to complete some industry funded studies if the results aren’t going their way and the distorting effect of regulatory policies on study design, such as regulatory demand for placebo controlled designs rather than more useful comparative research.